Design Shape and Dimension of Threshing Station Model Palm Oil Mill in PT. Perkebunan Nusantara V - PKS Sei Galuh Using Autodesk AutoCAD 2014 Software - Sofyan Arief, Dodi; Sihombing, Galuh Leonardo; Hamzah, Amir; , Andri (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2017)
Palm oil mills in PT. Perkebunan Nusantara V PKS - Sei Galuh is a producer of crude palm oil CPO (Crude Palm Oil), which consists of several stations the processing of palm oil, one of which is the threshing station. Threshing station is the station there is a separation palm kernel process with the cluster in a way slammed into a rotating drum. The purpose of this research is to design the shape and dimension of the station threshing model palm oil mill in PT. Perkebunan Nusantara V - PKS Sei Galuh with scale of 1: 8 using Autodesk Autocad 2014 Software. Design of shapes and dimension threshing station model is divided into three groups, namely the design shape and dimension of auto feeder, design shape and dimension of thresher and design shape and dimension of screw conveyor. The design shape and dimension of auto feeder are 2 units sprocket and 11 plate shaped profile L. The design shape and dimension of thresher is a diameter of 230 mm and a length 500 mm. The design shapes and dimension of screw conveyor are 3 screw with a diameter of 100 mm and a length of each screw is 156 mm, 160 mm and 156 mm. Cover on the design of the shape and dimension of screw conveyor U-shaped profile with a diameter of 120 mm and a length of 620 mm cover.